Tourists behavior towards purchasing souvenirs: the case study of Melaka / Khairunnisa Rapaee, Mohamad Idham Arif Abd Rashid and Zulaika Anuar - Rapaee, Khairunnisa; Abd Rashid, Mohamad Idham Arif; Anuar, Zulaika (2015)
This research is to investigate tourist behavior towards buying souvenirs at Central Melaka which is Bandar Hilir. The information related to this topic will be obtained from tourists around Bandar Hilir. The intention of the tourists behavior towards buying souvenirs are discussed in this research. The determination are identifed using Theory of Planned Behavior which consist of attitude towards behavior variable, subjective norms variable and perceived behavioral control variables which influenced the intention of tourist in buying souvenirs during their vacation at Bandar Hilir. Furthermore, the data are analyzed using WarpPLS-SEM. Besides that, the primarily data and secondary data are used and the data were collected accordingly. In addition, questionnaires has been distributed to the tourists around Bandar Hilir in order to get information regarding on the factors that influence tourists towards buying souvenirs. Finding suggested that the relationship of intention has been affected by the subjective norms factors and perceived behavioral control factors. However, the relationships of actual behaviour has been influenced by the intention.